Navigating the High Seas of Mental Health: Exploring the Prevalence of Depression, Stress, Anxiety, and Burnout Among Indian Seafarers - Kavita Sharma (International Journal of Public Health Excellence (IJPHE), 2024)
The primary objective of this study is to investigate the extent to which depression, stress, anxiety, and burnout in Indian seafarers. The study collected data from 109 Indian seafarers through Google Forms from March 2023 to April 2023. Descriptive statistics and inferential statistics were used to summarize the data based on selected demographic factors. The results showed that Indian seafarers suffered from mild depression (Mean =13.54) Seafarers also suffer from moderate levels of anxiety (Mean= 10.81). The levels of stress are found to be of normal level (Mean=13.28). The average scores for the components of burnout, namely Disengagement, and Exhaustion, among seafarers are 20.03 (SD= 3.673) and 20.43 (SD= 4.051) respectively. These findings suggest that seafarers exhibit moderate levels of burnout. Also, the correlational analysis shows a positive moderate correlation between total scores of depression, anxiety, stress, and components of Burnout with a value of 0.392 at a 1 % level of significance. The study highlights the need for mental health interventions and support services for seafarers to prevent and manage mental health issues in this population.